Callus induction from ovules of kenaf (Hibiscus cannabinus L.) - Ahmed Mahmood Ibrahim; Fatimah Kayat; Dwi Susanto; Mohammad Arifullah; Pedram Kashiani (2015)
Kenaf (Hibiscus cannabinus L.) is an important crop cultivated for fiber production. The haploid production using tissue culture technique is a fast and efficient tool for developing new varieties in comparatively short-time. Kenaf HF992 cultivar was chosen as an explants material, several trials were carried out to investigate the gynogenesis ability before we succeed to get high percentage of callus induction from ovule. Flower buds at the appropriate stage of ovule development were sterilized and the ovules were carefully excised from the flowers and underwent to various pretreatments and inoculated onto MS media supplemented with different combinations of Plant Growth Regulators (PGR) like NAA (a-naphthaleneacetic acid), BAP (N6-benzyladenine), 2iP (N6-(2-isopentenyl) adenine) and TDZ (Thidiazuron) and kept in the dark place for different periods before transferred to light conditions. The high frequency of callus induction (98%) was observed when the ovules collected from the flower bud size of 22-24 mm length after 2-4 weeks of the flower initiation and inculcated onto the optimized semi solid MS medium (3:1 gelrite:agar by weight) fortified with 3.0 mg L‾1 NAA+3.0 mg L‾1 2iP.